Study on the dynamic characteristics of rock surrounding a wellbore in energy storage areas during deep geothermal energy mining. - Chun Wang; Huai-Bin Wang; Mei-Zhi Xie; Zu-Qiang Xiong; Cheng Wang; Lu-Ping Cheng; Shuai-Fei Zhan (PLoS ONE, 2020)
Based on the engineering background in which the rock surrounding a wellbore is affected by a thermal shock, impact disturbances from drilling vibration, cyclic heat extraction and high temperature during hydrothermal geothermal energy mining, the environmental conditions in the shaft wall rock are simulated by means of high temperature, cooling, immersing granite in water with different curing temperatures and applying impact loads. Additionally, an experimental study on the mechanical characteristics of circular granite specimens under radial impact loads and in the heat treatment and water curing conditions is carried out. The results show that the inner diameters of the rings, heating temperatures, curing water temperatures and cycle heating times are less affected than other parameters by the impact load-strain curves of circular granite, which can generally be divided into three sections, i.e., the initial straight stage, nonlinear ascent yield stage and post-peak nonlinear decline stage. The factors in the test weaken the capacity of the circular granite to resist the impact, but the sizes of the inner diameters of the rings play a leading role. Dynamic tensile strain is generated in the inner wall along the impact direction during the impact, while compressive strain is produced on the inner wall in the vertical impact loading direction. By analysing the crack propagation and final failure mode of circular granite, it is found that dynamic tensile failures are generated, crack initiation starts from the inner wall along the impact loading direction, and the outer circle in the vertical direction lags behind. The crack starts early and develops quickly on one side of the transmission bar. Finally, the failure criterion is established on the basis of some assumptions and circular-granite deformation failure characteristics, and the parameters, measured by the Brazilian disk test, are reasonably verified via substitution into the failure criterion equation.